ANALYSIS OF OPTIMIZATION OF DI. YOGYAKARTA REGIONAL PROPERTY ASSETS IN KALIURANG AREA - Muhammad Safar Nasir; Firsty Ramadhona Amalia Lubis (Universitas Tidar, 2021)
The importance role of BMD (regional-owned assets) in supporting local governance, make its management becomes one of the indicators of the success of Regional Medium-Term Development Plan (RPJMD) DIY 2017-2022, with indicator: optimalization of local government assets with the enhancement of regional asset management effectivity, through the employment and cooperation with third party. Based upon that matter, strategic stages are required in the implementation of regional property assets management. As strategic step in optimalization and effectivity enhancement efforts in such management, comprehensive study is compulsory towards current utilized BMD or the idle BMD owned by DI. Yogyakarta local government, particularly for strategic BMD. From the analysis of Benefit Cost Ratio, it is indicated that the entire BMD assets, which become the object of the research, spend higher cost than the revenue. It demonstrates the non-optimal employment. From SWOT analysis, it can be identified that the advantage of designated BMD assets is on their utilization for tourism, hence the integrated asset management is required.